Assessment of geogenic radon potential with activation of advective soil air flow - I. V. Yarmoshenko; G. P. Malinovsky; I. A. Yurkov; V. S. Izgagin (Радиационная гигиена)
Prediction of radon potential and justification of measures for reducing radon concentration in buildings necessitate the study of soil radon transport. The article presents an approach to estimating the geogenic radon potential of a site based on the study of the dependence of the radon flux from the soil on the pressure gradient. The efficacy of the method of radon flux density measurement with artificial activation of controlled advective air flow from the soil into the accumulation chamber was evaluated at an experimental site. The measuring installation consisted of a large-volume accumulation chamber (200 l), a system of pumps, flow meters, and a differential manometer. The results of measurements at 12 points on the experimental site yielded a number of values, including advective radon flux density as a function of pressure difference between the accumulation chamber and the atmosphere (in the range 4–20 Pa), radon concentration in soil air, and resistance to air flow in the soil-chamber system. The results demonstrate that at the investigated site, the potential advective radon flux density significantly exceeds the diffusive radon flux density: the corresponding radon flux density ranges are 23–870 mBq/(m2 s) and 5.5–7.0 mBq/(m2 s), respectively. The air flow resistance in the system of the soil measurement chamber varies depending on the meteorological conditions, with a range from 93 to 2400 kPa/(m3·s-1). On average, under dry conditions, the resistance to airflow is 4.8 times lower than in rain. The radon concentration in the soil varies from 0.6 to 3.2 kBq/m3, with an arithmetic mean of 1.4 kBq/m3. The dependence of the advective radon flux density, normalized to a pressure difference of 1 Pa, on the air flow resistance follows the Darcy’s law. This dependence, taking into account the soil radon concentration, characterizes the geogenic radon potential at the site. The advantages and disadvantages of the method of geogenic radon potential estimation based on the artificial activation of the pressure gradient in the measurement system are discussed.